A Modular Synthesis of Conformationally Preorganised Extended β‐Strand Peptidomimetics. Issue 42 (1st September 2015) - Yamashita, Tohru; Knipe, Peter C.; Busschaert, Nathalie; Thompson, Sam; Hamilton, Andrew D.
Abstract Invited for the cover of this issue is the group of Andrew D. Hamilton and Sam Thompson at the University of Oxford (UK). The image depicts a new class of conformationally constrained β‐strand mimetics mediating the interaction between two subunits of a protein that controls transcription. Read the full text of the article at 10.1002/chem.201501366.